Method for preparing heat dissipation plate
By roughening the surface of the copper plate and adding copper metal particles to the semi-solid aluminum alloy paste, the problem of uneven interface bonding strength and thermal resistance of the copper-aluminum composite heat dissipation plate is solved, and a higher interface bonding strength and Thermal conductivity.
Patent Information
- Application Number
- CN202411551883.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-01
AI Technical Summary
There are uneven problems with the interface combination strength and interface thermal resistance of existing copper-aluminum composite heat dissipation plates, which affects its performance.
By roughening the surface of the copper plate and adding 0.3-0.5% of copper metal particles with an average particle size of 5-10μm to the semi-solid aluminum alloy paste, a tighter interface bonding layer is formed to improve interface bonding strength and heat conduction. coefficient.
A more uniform interface combination strength and thermal conductivity are achieved, reducing the generation of air holes and shrinkage holes, and improving the overall performance of the heat dissipation plate.
Smart Images

Figure CN119035510B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of metal composite material manufacturing, and in particular to a method for preparing a heat dissipation plate. Background Art
[0002] Copper-aluminum composite heat sinks combine the advantages of copper and aluminum, such as copper's electrical conductivity and heat transfer properties with aluminum's lightweight and corrosion resistance, and can help further reduce heat sink costs. However, due to the significant differences between copper and aluminum and their low mutual solubility, the copper-aluminum composite heat sink formed through welding and other methods suffers from poor interface consistency, uneven distribution of heat conduction and resistance, and significant differences in physical properties between copper and aluminum, which can affect the performance of the copper-aluminum composite heat sink.
[0003] The applicant disclosed a copper-aluminum composite metal plate and a casting method and its application in a radiator in CN118180357A. By pouring semi-solid aluminum onto the surface of copper after surface roughening treatment and then ultrasonically obtaining a composite metal plate, a composite metal plate with high interface bonding strength and thermal conductivity was obtained. However, the solid phase fraction during semi-solid aluminum casting has a significant impact on the interface bonding strength, interface thermal resistance and interface microstructure of the copper-aluminum composite metal plate. The effect of the solid phase fraction on the interface bonding strength is manifested as follows: when the solid phase fraction in the semi-solid aluminum paste is low, the liquid phase in the aluminum paste accounts for a large proportion and has better fluidity, but it may lead to a weakening of the mechanical locking effect at the copper-aluminum interface, thereby reducing the interface bonding strength; as the solid phase fraction increases, the solid phase particles in the aluminum paste increase, and these particles form a tighter physical connection at the copper-aluminum interface, enhancing the interface bonding strength; however, an excessively high solid phase fraction may cause the aluminum paste to have a reduced fluidity, which is not conducive to the uniform distribution of the aluminum liquid in the copper plate, thereby affecting the interface bonding quality. The effect of the solid phase fraction on interfacial thermal resistance is manifested as follows: changes in the solid phase fraction affect the thermal conductivity of the copper-aluminum interface. A low solid phase fraction may lead to more pores and defects at the interface, increasing thermal resistance. As the solid phase fraction increases, the pores and defects at the interface decrease, the heat conduction path becomes smoother, and thus the interfacial thermal resistance is reduced. The effect of the solid phase fraction on the interface microstructure is manifested as follows: at low solid phase fractions, a thin reaction layer or intermetallic compound layer may form at the interface. As the solid phase fraction increases, the interfacial reaction becomes more complete, and the type and amount of intermetallic compounds will change, affecting the microstructure and performance of the interface. Therefore, simply adjusting the solid phase content cannot further improve its interfacial bonding strength and interfacial thermal resistance.
[0004] Therefore, it is necessary to provide a method for preparing a heat dissipation plate. Summary of the Invention
[0005] In order to further improve the interface bonding strength and interface of the copper-aluminum composite heat sink, it is necessary to provide a preparation method of the heat sink.
[0006] The present invention provides a method for preparing a heat dissipation plate, comprising the following steps:
[0007] At least one surface of a copper plate is roughened to obtain a roughened surface, the copper plate is placed in a mold for preheating, an aluminum alloy is heated to obtain an aluminum alloy melt having a temperature of 10-20°C above the liquidus, 0.3-0.5% by mass of metal particles with an average particle size of 5-10 μm are added to the aluminum alloy melt, and the aluminum alloy melt is prepared into a semi-solid aluminum alloy slurry with a solid phase fraction of 15-35%, wherein the metal particles contain copper, and the semi-solid aluminum alloy slurry is poured onto the roughened surface to form an aluminum layer, and the heat sink is obtained by die casting.
[0008] Beneficial effects of the present invention: When an aluminum composite layer is formed on the surface of a copper layer by semi-solid die-casting according to current technology, if a semi-solid aluminum alloy slurry with a high solid phase fraction is used, the slurry will not be able to fully fill the mold due to poor fluidity, and pores will easily be generated in some areas. If a semi-solid aluminum alloy slurry with a low solid phase fraction is used, shrinkage cavities will be generated near the interface bonding layer due to volume shrinkage during the cooling process. Both pores and shrinkage cavities will lead to a decrease in the thermal conductivity and interface bonding strength of the heat sink. Conventional adjustment of the solid phase fraction cannot reduce the generation of pores and shrinkage cavities at the same time, and various parameters need to be strictly controlled, resulting in large batch differences. The present application adds metal particles with an average particle size of 5-10 μm at a mass fraction of 0.3-0.5% during the preparation of a semi-solid aluminum alloy slurry. The metal particles contain copper. The metal particles are fully dispersed in the slurry during the slurrying process. During the casting process, the density of the metal particles is much greater than the density of the aluminum alloy, so the metal particles are deposited at the bottom of the slurry. The average particle size of the metal particles is smaller than the average particle size of the solid aluminum metal particles. The metal particles can replace part of the liquid phase to fill the gap between the rough surface and the solid aluminum metal particles, reduce the gaps caused by the shrinkage of the liquid phase after cooling, form a tighter interface bonding layer, and improve the interface bonding strength and thermal conductivity. The above method uses a semi-solid slurry with high fluidity to avoid pores caused by the inability of the slurry to fully fill the mold, and solves the problem of a large number of shrinkage cavities generated during the cooling process of a semi-solid slurry with a low solid phase fraction.
[0009] Furthermore, the metal particles include large particles and small particles, the average particle size of the large particles is 10 μm, and the average particle size of the small particles is 5 μm. By using metal particles of various average particle sizes to form a gradation effect, the physical locking effect is further enhanced to provide interfacial bonding strength. Furthermore, the mass ratio of the large particles to the small particles is 1:(3-7). The metal particles with the above mass ratio can provide stronger interfacial bonding strength.
[0010] Furthermore, the semi-solid aluminum alloy slurry is prepared by ultrasonic stirring, wherein the frequency of the ultrasonic wave is 20-35 kHz and the ultrasonic treatment time is 10-25 seconds. The ultrasonic stirring method helps to disperse the metal particles in the semi-solid slurry.
[0011] Furthermore, the roughness Ra of the roughened surface is 10-20, and Rz is 15-25. Roughness Ra and Rz have a significant impact on the interface bonding strength and interface heat transfer coefficient.
[0012] Furthermore, the aluminum alloy is 6061 aluminum alloy. 6061 aluminum alloy has excellent corrosion resistance and processing properties, and the semi-solid slurry prepared therefrom has excellent fluidity and can reduce the generation of shrinkage cavities.
[0013] Furthermore, the roughening treatment is laser texturing, which can precisely control the roughness of the rough surface. By heating, melting, and resolidifying the rough surface with a laser beam, a tiny concave-convex structure can be formed, thereby improving the bonding strength of the bonding interface.
[0014] Furthermore, die casting includes die casting using a die casting machine at a pressure of 400-500 MPa, a speed of 800-1000 mm / min, and a holding time of 20-30 seconds. Within these pressure and speed ranges, shrinkage cavities can be reduced, and an appropriate holding time ensures sufficient contact between the materials on both sides of the interface layer without causing excessive cooling of the metal and other adverse reactions.
[0015] Furthermore, the roughness of the roughened surface is Ra 17.8-18.3 and Rz 24.3-24.9. The roughened surface can better form a physical interlocking structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a diagram of the heat sink interface organization structure of Example 1.
[0017] Figure 2 This is the interface organizational structure diagram of the heat sink of comparative example 1. DETAILED DESCRIPTION
[0018] For ease of understanding of the present application, the present application will be described more fully below. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0019] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of such features. In the description of the application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of this application, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.
[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application pertains. The terms used herein in the specification of this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0021] In this application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0022] In this application, when referring to numerical ranges, unless otherwise specified, the numerical ranges are considered continuous and include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe a feature or characteristic, the ranges can be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges subsumed therein.
[0023] Unless otherwise specified, the percentage contents mentioned in this application refer to mass percentage for solid-liquid mixture and solid-solid mixture, and refer to volume percentage for liquid-liquid mixture.
[0024] The percentage concentrations mentioned in this application, unless otherwise specified, refer to the final concentration, which refers to the percentage of the added component in the system after the addition of the component.
[0025] The temperature parameters in this application, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows for temperature fluctuations within the precision range of instrument control.
[0026] The "particles" referred to in this application, or materials with a defined average particle size distribution, are not necessarily spherical in shape but may be irregular, primary or secondary. The average particle size of irregular particles is the average of their maximum and minimum diameters.
[0027] Example 1: Roughening of a Copper Plate: After cutting, T2 copper was textured on an abrasive belt, and one side was laser textured. The laser power density was set to 45 kW / cm², the pulse frequency was set to 95 Hz, and the laser scanning speed was set to 15 mm / s. The surface roughness of the treated copper was Ra 18.2 and Rz 24.7. The copper was then pickled and dried. The pickling formula (in volume percentage) was: 15% sulfuric acid, 1% glycolic acid, 2.5% citric acid, and the balance was water. The pickling temperature was 40°C and the time was 5 minutes.
[0028] Preparation of an aluminum alloy melt: 6061 aluminum alloy was heated to 750° C. to obtain an aluminum alloy melt, which was then cooled to 720° C. and degassed and refined. When the temperature of the melt was 10° C. above the liquidus, 0.5% by mass of copper metal particles having an average particle size of 5 μm (the copper metal particles in all embodiments and comparative examples were made of T2 copper) were added to the melt, and the melt was kept warm for later use.
[0029] Copper plate preheating: The mold temperature is 350℃, the surface pretreated copper plate is placed in the mold, and heated under nitrogen protection for 60s;
[0030] Ultrasonic preparation of semi-solid aluminum alloy slurry: placing an ultrasonic probe in the aluminum alloy melt and applying ultrasound at an ultrasonic frequency of 25 kHz, an ultrasonic time of 20 s, and a power of 2000 W to obtain a semi-solid aluminum alloy slurry with a solid phase fraction of 35%;
[0031] Casting and die-casting: The semi-solid aluminum alloy slurry is cast on the rough surface of a preheated copper plate and die-casted using a die-casting machine at a pressure of 450 MPa, a speed of 900 mm / min, and a holding time of 30 s to obtain a heat sink.
[0032] Example 2: Roughening of a Copper Plate: After cutting, T2 copper was textured on an abrasive belt, and one side was laser textured. The laser power density was set to 45 kW / cm², the pulse frequency was set to 95 Hz, and the laser scanning speed was set to 15 mm / s. The surface roughness of the treated copper was Ra 18.3 and Rz 24.9. The copper was then pickled and dried. The pickling formula (in volume percentage) was: 15% sulfuric acid, 1% glycolic acid, 2.5% citric acid, and the balance was water. The pickling temperature was 40°C and the time was 5 minutes.
[0033] Preparation of aluminum alloy melt: 6061 aluminum alloy is heated to 750°C to obtain an aluminum alloy melt, which is then cooled to 720°C for degassing and refining. When the melt temperature is 20°C above the liquidus, 0.3% by mass of copper metal particles with an average particle size of 5 μm are added to the melt, and the melt is kept warm for later use.
[0034] Copper plate preheating: The mold temperature is 330℃, the surface pretreated copper plate is placed in the mold, and heated under nitrogen protection for 60s;
[0035] Ultrasonic preparation of semi-solid aluminum alloy slurry: placing an ultrasonic probe in the aluminum alloy melt and applying ultrasound at an ultrasonic frequency of 25 kHz, an ultrasonic time of 20 s, and a power of 2000 W to obtain a semi-solid aluminum alloy slurry with a solid phase fraction of 35%;
[0036] Casting and die-casting: The semi-solid aluminum alloy slurry is cast on the rough surface of a preheated copper plate and die-casted using a die-casting machine at a pressure of 500 MPa, a speed of 1000 mm / min, and a holding time of 20 s to obtain a heat sink.
[0037] Example 3: Roughening treatment of copper plate: After T2 copper was cut and textured on an abrasive belt, one side was laser textured. The laser power density was set to 35kW / cm², the pulse frequency was set to 95Hz, and the laser scanning speed was set to 15mm / s. The surface roughness of the treated copper was Ra 10.4 and Rz 15.3. The copper was then pickled and dried. The pickling formula (in volume percentage) was: 15% sulfuric acid, 1% glycolic acid, 2.5% citric acid, and the balance was water. The pickling temperature was 40°C and the time was 5 minutes.
[0038] Preparation of aluminum alloy melt: 6061 aluminum alloy is heated to 750°C to obtain an aluminum alloy melt, which is then cooled to 720°C for degassing and refining. When the melt temperature is 10°C above the liquidus, 0.5% by mass of copper metal particles with an average particle size of 5 μm are added to the melt and the melt is kept warm for later use.
[0039] Copper plate preheating: The mold temperature is 350℃, the surface pretreated copper plate is placed in the mold, and heated under nitrogen protection for 60s;
[0040] Ultrasonic preparation of semi-solid aluminum alloy slurry: placing an ultrasonic probe in the aluminum alloy melt and applying ultrasound at an ultrasonic frequency of 25 kHz, an ultrasonic time of 20 s, and a power of 2000 W to obtain a semi-solid aluminum alloy slurry with a solid phase fraction of 35%;
[0041] Casting and die-casting: The semi-solid aluminum alloy slurry is cast on the rough surface of a preheated copper plate and die-casted using a die-casting machine at a pressure of 450 MPa, a speed of 900 mm / min, and a holding time of 30 s to obtain a heat sink.
[0042] Example 4: Roughening of a Copper Plate: After cutting, T2 copper was textured on an abrasive belt, and one side was laser textured. The laser power density was set to 45 kW / cm², the pulse frequency was set to 95 Hz, and the laser scanning speed was set to 15 mm / s. The surface roughness of the treated copper was Ra 18.2 and Rz 24.7. The copper was then pickled and dried. The pickling formula (in volume percentage) was: 15% sulfuric acid, 1% glycolic acid, 2.5% citric acid, and the balance was water. The pickling temperature was 40°C and the time was 5 minutes.
[0043] Preparation of aluminum alloy melt: 6061 aluminum alloy is heated to 750°C to obtain an aluminum alloy melt, which is then cooled to 720°C for degassing and refining. When the melt temperature is 10°C above the liquidus, 0.5% by mass of copper metal particles with an average particle size of 10 μm are added to the melt, and the melt is kept warm for later use.
[0044] Copper plate preheating: The mold temperature is 350℃, the surface pretreated copper plate is placed in the mold, and heated under nitrogen protection for 60s;
[0045] Ultrasonic preparation of semi-solid aluminum alloy slurry: placing an ultrasonic probe in the aluminum alloy melt and applying ultrasound at an ultrasonic frequency of 25 kHz, an ultrasonic time of 20 s, and a power of 2000 W to obtain a semi-solid aluminum alloy slurry with a solid phase fraction of 35%;
[0046] Casting and die-casting: The semi-solid aluminum alloy slurry is cast on the rough surface of a preheated copper plate and die-casted using a die-casting machine at a pressure of 450 MPa, a speed of 900 mm / min, and a holding time of 30 s to obtain a heat sink.
[0047] Example 5: Roughening treatment of copper plate: After cutting, T2 copper was textured on an abrasive belt, and one side was laser textured. The laser power density was set to 45kW / cm², the pulse frequency was set to 95Hz, and the laser scanning speed was set to 15mm / s. The surface roughness of the treated copper was Ra 17.8 and Rz 24.2. The copper was then pickled and dried. The pickling formula (in volume percentage) was: 15% sulfuric acid, 1% glycolic acid, 2.5% citric acid, and the balance was water. The pickling temperature was 40°C and the time was 5 minutes.
[0048] Preparation of aluminum alloy melt: 6061 aluminum alloy is heated to 750°C to obtain an aluminum alloy melt. After cooling to 720°C, degassing and refining are performed. When the temperature of the melt is 10°C above the liquidus, 0.5% by mass of copper metal particles (including small particles with an average particle size of 5 μm and large particles with an average particle size of 10 μm, with a mass ratio of 3:1) are added to the melt and the melt is kept warm for later use.
[0049] Copper plate preheating: The mold temperature is 350℃, the surface pretreated copper plate is placed in the mold, and heated under nitrogen protection for 60s;
[0050] Ultrasonic preparation of semi-solid aluminum alloy slurry: placing an ultrasonic probe in the aluminum alloy melt and applying ultrasound at an ultrasonic frequency of 25 kHz, an ultrasonic time of 20 s, and a power of 2000 W to obtain a semi-solid aluminum alloy slurry with a solid phase fraction of 35%;
[0051] Casting and die-casting: The semi-solid aluminum alloy slurry is cast on the rough surface of a preheated copper plate and die-casted using a die-casting machine at a pressure of 450 MPa, a speed of 900 mm / min, and a holding time of 30 s to obtain a heat sink.
[0052] Example 6: Roughening treatment of copper plate: After cutting, T2 copper was textured on an abrasive belt, and one side was laser textured. The laser power density was set to 45kW / cm², the pulse frequency was set to 95Hz, and the laser scanning speed was set to 15mm / s. The surface roughness of the treated copper was Ra 17.9 and Rz 24.3. The copper was then pickled and dried. The pickling formula (in volume percentage) was: 15% sulfuric acid, 1% glycolic acid, 2.5% citric acid, and the balance was water. The pickling temperature was 40°C and the time was 5 minutes.
[0053] Preparation of aluminum alloy melt: 6061 aluminum alloy is heated to 750°C to obtain an aluminum alloy melt. After cooling to 720°C, degassing and refining are performed. When the temperature of the melt is 10°C above the liquidus, 0.5% by mass of copper metal particles (including small particles with an average particle size of 5 μm and large particles with an average particle size of 10 μm, with a mass ratio of 7:1) are added to the melt and the melt is kept warm for later use.
[0054] Copper plate preheating: The mold temperature is 350℃, the surface pretreated copper plate is placed in the mold, and heated under nitrogen protection for 60s;
[0055] Ultrasonic preparation of semi-solid aluminum alloy slurry: placing an ultrasonic probe in the aluminum alloy melt and applying ultrasound at an ultrasonic frequency of 25 kHz, an ultrasonic time of 20 s, and a power of 2000 W to obtain a semi-solid aluminum alloy slurry with a solid phase fraction of 35%;
[0056] Casting and die-casting: The semi-solid aluminum alloy slurry is cast on the rough surface of a preheated copper plate and die-casted using a die-casting machine at a pressure of 450 MPa, a speed of 900 mm / min, and a holding time of 30 s to obtain a heat sink.
[0057] Example 7: Roughening treatment of copper plate: After cutting, T2 copper was textured on an abrasive belt, and one side was laser textured. The laser power density was set to 45kW / cm², the pulse frequency was set to 95Hz, and the laser scanning speed was set to 15mm / s. The surface roughness of the treated copper was Ra 17.9 and Rz 24.3. The copper was then pickled and dried. The pickling formula (in volume percentage) was: 15% sulfuric acid, 1% glycolic acid, 2.5% citric acid, and the balance was water. The pickling temperature was 40°C and the time was 5 minutes.
[0058] Preparation of aluminum alloy melt: 6061 aluminum alloy is heated to 750°C to obtain an aluminum alloy melt. After cooling to 720°C, degassing and refining are performed. When the temperature of the melt is 10°C above the liquidus, 0.5% by mass of copper metal particles (including small particles with an average particle size of 5 μm and large particles with an average particle size of 10 μm, with a mass ratio of 7:1) are added to the melt and the melt is kept warm for later use.
[0059] Copper plate preheating: The mold temperature is 350℃, the surface pretreated copper plate is placed in the mold, and heated under nitrogen protection for 60s;
[0060] Ultrasonic preparation of semi-solid aluminum alloy slurry: placing an ultrasonic probe in the aluminum alloy melt and applying ultrasound at an ultrasonic frequency of 25 kHz, an ultrasonic time of 12 s, and a power of 2000 W to obtain a semi-solid aluminum alloy slurry with a solid phase fraction of 15%;
[0061] Casting and die-casting: The semi-solid aluminum alloy slurry is cast on the rough surface of a preheated copper plate and die-casted using a die-casting machine at a pressure of 450 MPa, a speed of 900 mm / min, and a holding time of 30 s to obtain a heat sink.
[0062] Comparative Example 1: Roughening of a Copper Plate: After cutting, T2 copper was textured on an abrasive belt. One side of the copper plate was then laser textured. The laser power density was set to 45 kW / cm², the pulse frequency was set to 95 Hz, and the laser scanning speed was set to 15 mm / s. The surface roughness of the treated copper plate was Ra 18.2 and Rz 25. The plate was then pickled and dried. The pickling formula (by volume percentage) was: 15% sulfuric acid, 1% glycolic acid, 2.5% citric acid, and the balance was water. The pickling temperature was 40°C and the pickling time was 5 minutes.
[0063] Preparation of aluminum alloy melt: 6061 aluminum alloy is heated to 750°C to obtain aluminum alloy melt, and then cooled to 720°C for degassing and refining. When the temperature of the melt is 10°C above the liquidus, it is kept warm for standby use;
[0064] Copper plate preheating: The mold temperature is 350℃, the surface pretreated copper plate is placed in the mold, and heated under nitrogen protection for 60s;
[0065] Ultrasonic preparation of semi-solid aluminum alloy slurry: placing an ultrasonic probe in the aluminum alloy melt and applying ultrasound at an ultrasonic frequency of 25 kHz, an ultrasonic time of 20 s, and a power of 2000 W to obtain a semi-solid aluminum alloy slurry with a solid phase fraction of 35%;
[0066] Casting and die-casting: The semi-solid aluminum alloy slurry is cast on the rough surface of a preheated copper plate and die-casted using a die-casting machine at a pressure of 450 MPa, a speed of 900 mm / min, and a holding time of 30 s to obtain a heat sink.
[0067] Comparative Example 2: Roughening of a Copper Plate: After cutting, T2 copper was textured on an abrasive belt. One side of the copper plate was then laser textured. The laser power density was set to 45 kW / cm², the pulse frequency was set to 95 Hz, and the laser scanning speed was set to 15 mm / s. The surface roughness of the treated copper plate was Ra 18.2 and Rz 25. The plate was then pickled and dried. The pickling formula (by volume percentage) was: 15% sulfuric acid, 1% glycolic acid, 2.5% citric acid, and the balance was water. The pickling temperature was 40°C and the pickling time was 5 minutes.
[0068] Preparation of aluminum alloy melt: 6061 aluminum alloy is heated to 750°C to obtain aluminum alloy melt, and then cooled to 720°C for degassing and refining. When the temperature of the melt is 10°C above the liquidus, it is kept warm for standby use;
[0069] Copper plate preheating: The mold temperature is 350℃, the surface pretreated copper plate is placed in the mold, and heated under nitrogen protection for 60s;
[0070] Ultrasonic preparation of semi-solid aluminum alloy slurry: placing an ultrasonic probe in the aluminum alloy melt and applying ultrasound at an ultrasonic frequency of 25 kHz, an ultrasonic time of 12 s, and a power of 2000 W to obtain a semi-solid aluminum alloy slurry with a solid phase fraction of 15%;
[0071] Casting and die-casting: The semi-solid aluminum alloy slurry is cast on the rough surface of a preheated copper plate and die-casted using a die-casting machine at a pressure of 450 MPa, a speed of 900 mm / min, and a holding time of 30 s to obtain a heat sink.
[0072] The interface bonding force, tensile strength and thermal conductivity of the heat dissipation plates of Examples 1-7 and Comparative Examples 1-2 were tested.
[0073] Test methods: Interface bonding strength (tested using the peeling method in GJB 446-1988; the peeling strength represents the interface bonding strength in this example) and thermal conductivity of the copper-aluminum composite metal plate (measured using ISO 8301 AMD 1-2010). The test results are shown in Table 1.
[0074] Table 1
[0075] According to the data in Table 1, the thermal conductivity and interface bonding strength of the heat sinks of Examples 1-2 and 4-7 are higher than those of Comparative Example 1. This is because in the process of preparing the semi-solid aluminum alloy slurry, the present solution adds 0.3-0.5% of metal particles with an average particle size of 5-10 μm. The metal particles contain copper. The metal particles are fully dispersed in the slurry during the slurry preparation process. During the casting process, the density of the metal particles is much greater than the density of the aluminum alloy. Therefore, the metal particles are deposited at the bottom of the slurry. The average particle size of the metal particles is smaller than the average particle size of the solid aluminum metal particles. The metal particles can replace part of the liquid phase to fill the gap between the rough surface and the solid aluminum metal particles, reduce the gaps caused by the contraction of the liquid phase after cooling, form a tighter interface bonding layer, and improve the interface bonding strength and thermal conductivity. Figure 1 As shown, no obvious bubbles were found at the interface of the heat sink in Example 1, the interface transition layer was uniform, and copper and aluminum were fully diffused to form an intermetallic compound layer and a diffusion layer. Figure 2 As shown, obvious bubbles appeared on the interface of the heat sink in Example 2. This is because its higher liquid phase fraction produced shrinkage cavities in some areas during the cooling process. Comparative Example 2 used a semi-solid aluminum alloy slurry with a lower solid phase fraction than Comparative Example 1. Although it helped to evenly distribute the slurry on the rough surface and fill the space between the solid copper and aluminum solid phase particles, it was easy to produce shrinkage cavities at the interface after cooling, resulting in a decrease in interfacial bonding strength and thermal conductivity. Although Example 7 also used a semi-solid aluminum alloy slurry with a lower solid phase fraction, because its copper metal particles can replace part of the liquid phase to fill the gap between the rough surface and the solid aluminum metal particles, reducing the gaps caused by the contraction of the liquid phase after cooling, it can still obtain a heat sink with better thermal conductivity and interfacial bonding strength.
[0076] The roughness Ra and Rz of the rough surface of Example 3 are relatively small, which is not conducive to forming a physical interlocking structure, resulting in poor thermal conductivity and interface bonding strength. Examples 5-6 have better performance than Examples 1 and 4. This is because the use of metal particles with various average particle sizes creates a gradation effect, further enhancing the physical locking effect and improving interface bonding strength.
[0077] The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0078] The above-described embodiments merely illustrate several implementations of the present invention, and while their descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, all of which fall within the scope of protection of the present invention. Therefore, the scope of protection of the patent for this invention shall be determined by the appended claims.
Claims
1. A method for preparing a heat dissipation plate, characterized in that: The following steps are involved: Roughening at least one surface of a copper plate to obtain a roughened surface, placing the copper plate in a mold for preheating, heating an aluminum alloy to obtain an aluminum alloy melt having a temperature of 10-20° C. above the liquidus, adding 0.3-0.5% by mass of copper metal particles to the aluminum alloy melt, wherein the copper metal particles include large particles and small particles, wherein the average particle size of the large particles is 10 μm, the average particle size of the small particles is 5 μm, and the mass ratio of the large particles to the small particles is 1:(3-7), and the aluminum alloy is The melt is prepared into a semi-solid aluminum alloy slurry with a solid phase fraction of 15-35%, and the semi-solid aluminum alloy slurry is prepared by an ultrasonic stirring method, the frequency of the ultrasonic wave is 20-35KHz, and the ultrasonic treatment time is 10-25s. The semi-solid aluminum alloy slurry is poured on the roughened surface to form an aluminum layer, and the heat sink is obtained by die casting. The die casting includes: die casting molding using a die casting machine, the pressure is 400-500MPa, the speed is 800-1000mm / min, and the holding time is 20-30s.
2. The preparation method according to claim 1, characterized in that The roughness Ra of the roughened surface is 10-20, and Rz is 15-25.
3. The preparation method according to claim 1, characterized in that The aluminum alloy melt is prepared into a semi-solid aluminum alloy slurry with a solid phase fraction of 15-20%.
4. The preparation method according to claim 1, characterized in that The aluminum alloy is 6061 aluminum alloy.
5. The preparation method according to claim 1, characterized in that The roughening process is laser texturing process.
6. The preparation method according to claim 1, characterized in that The roughness Ra of the roughened surface is 17.8-18.3, and Rz is 24.3-24.9.
Citation Information
Patent Citations
Semi-solid state communication heat radiation housing and production method thereof
CN107787147A
Spherical intermetallic compound particle reinforced aluminum-based composite material and preparation method thereof
CN115505798A
Copper-aluminum composite metal plate, casting forming method and application of copper-aluminum composite metal plate in radiator
CN118180357A